Neural Trauma and Gendered Oppression in Toni Morrison’s Beloved: A Neurofeminist Analysis of Memory, Cognition and Agency in Enslaved Women - Muhammad Ajmal; Atiqa Kanwal; Rozina Bibi (Research Journal of Psychology, 2025)
This study aims to investigate the convergence of neural trauma, gendered oppression and memory in Toni Morrison’s Beloved through the perspective of neurofeminism. Bridging feminist critiques of neuroscience with trauma theory, the research assesses the cognitive and psychological effects of slavery on enslaved women, specifically Sethe and Denver in Beloved. This research analyzes the novel’s nonlinear narrative structure and the characters’ psychological struggles in light of the traumatic neurological mechanisms, such as memory fragmentation, dissociation, and post-traumatic stress disorder (PTSD). It also asks how gendered oppression exacerbates neural trauma, hindering agency and entrenching systemic violence against Black women. The idea of neuroplasticity is also touched on, with the interpersonal aspects of cognitive resilience and emotional repair developed into a model of communal storytelling and kinship. At the same time, this interrogation — through the lens of neurofeminism — reconsiders the often cognitive-centric neuroscientific paradigms that, at times, beyond the bounds of historical context, have acted as if trauma could be understood independent of the sociopolitical context in which its constituents developed. This study concludes that Morrison’s Beloved is a great literary meditation on the neurological traumas of enslavement and the agony toward selfhood and healing.